Actinic comedonal plaque - Milano, A. (European Journal of Pediatric Dermatology, 2012)
A 46-year-old man presented from the age of 43 an asymptomatic plaque of the left thigh that gradually enlarged until reaching the current size with a diameter of 12 cm. The patient consulted numerous medical centers; a mycological examination grew Rhodotorula rubra. He underwent two histological examinations that showed elastosis, broken epidermal cysts with granulomatous, giant cell inflammatory reaction (Fig. 4) and excluded the presence of fungi. The physical examination (Fig. 1, 2, 3) showed an alopecic plaque with well defined borders, with numerous punctate scars, blackheads, folliculitis and large granulomas. The clinical and histological findings led to the diagnosis of actinic comedonal plaque. We did not recommend sun exposure in summer and prescribed topical tretinoin in the cold period.